Task management model for Cleevio company s.r.o - Dusbaba, Matěj; Oškrdal, Václav; Křemenák, Jakub; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
This bachelor's thesis occupies with a task management model in the company Cleevio s.r.o. which specializes in a development of tailor-made mobile applications. A primary problem is a current absence of basic rules, principles, and use of necessary tools.The aim of the thesis is to analyse the current situation and suggest a task management model suitable for effective management of not only company's projects but also its employees. The theoretical part of the thesis focuses on the introduction of basic terms such as task management itself and definition of subjects as a team etc. Then the thesis introduces the company and its current situation. It further specifies and suggests an ideal model which could help the company to become more effective. The author also includes a procedure for implementation of the model and chooses a suitable tool which can be used to realize the plan. The selection of the suitable tool is based on the suggested model and the company's needs. The author chooses well-known SaaS tool Trello. At the end of the thesis, the author assesses the proposed model and if it is applied in time, the thesis will evaluate its real contribution. The contribution hangs upon the optimization, increase in the effectiveness of task distribution and its record, control and reporting.
Vedoucí práce: Václav Oškrdal
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses